Stability Analysis of a Class of Nonlinear Discrete Systems with Impulsive Effects - Chen, Y.; Xu, Honglei; Teo, Kok Lay (Watam Press, 2010)
This paper investigates stability problems of nonlinear discrete systems with impulsive effects. The impulse is described by a nonlinear function of the state vector x. Employing a Lyapunov functional-based method, sufficient conditions for asymptotical stability of this class of discrete systems are derived. Finally, a numerical example is presented to illustrate the efficiency of our results.